New insights in the Spanish gene pool of olive (Olea europaea L.) preserved ex situ and in situ based on high-throughput molecular markers - Gómez-Gálvez, Francisco Jesús; Ninot, Antònia; Rodríguez, Juan Cano; Compañ, Sergio Paz; Andreva, Javier Ugarte; Rubio, Javier Alfonso García; Aragón, Isis Pinilla; Viñuales-Andreu, Javier; Casanova-Gascón, José; Šatović, Zlatko; Lorite, Ignacio Jesús; De la Rosa-Navarro, Raúl; et al. (Frontiers in Plant Science, 2024)
In Spain, several several local studies have highlighted the likely presence of unknown olive cultivars distinct from the approximately 260 ones previously described in the literature. Furthermore, recent advancements in identification techniques have significantly enhanced in terms of efficacy and precision. This scenario motivated a new nationwide prospecting effort aimed at recovering and characterizing new cultivated germplasm using high-throughput molecular markers. In the present study, the of 96 EST-SNP markers allowed the identification of a considerable amount of new material (173 new genotypes) coming from areas with low cultivation intensification of production pressure in different regions of Spain. As a result, the number of distinct national genotypes documented in the World Olive Germplasm Bank of IFAPA, Córdoba (WOGBC-ESP046) increased to 427. Likewise, 65 and 24 new synonymy and homonymy cases were identified, respectively. This rise in the number of different national cultivars allowed to deepen the knowledge about the underlying genetic structure. The great genetic variability of Spanish germplasm was confirmed, and a new hot spot of diversity was identified in the northern regions of La Rioja and Aragon. Analysis of the genetic structure showed a Con formato: Fuente: Cursiva Con formato: Fuente: Cursiva Con formato: Fuente: Cursiva 2 This is a provisional file, not the final typeset article clear separation between the germplasm of southern and northern-northeastern Spain and indicated a significantly higher level of admixture in the latter. Given the expansion of modern olive cultivation with only a few cultivars, this cryptic germplasm is in great danger of disappearing. This underlines the fact that maintaining as many cultivars as possible will increase the genetic variability of the olive gene pool to meet the future challenges of olive cultivation.